Terceiro setor: desafios e perspectivas constitucionais - Barbieri, Carla Bertucci (2006)
The present dissertation aims to point out juridical outlines of the Third Sector in Brazil, its present moment, challenges and perspectives in constitutional reference through the contextualization of social-political-economical aspects of the theme. As a form of approach and aversion to ideological usage, motivated by the neo-liberal project, which is assumed about the Third Sector, we make use of the Brazilian constitutional framework, facing five crucial issues: 1) Can the Third Sector existence be defended? 2) What is its concept? What are its weaknesses? 3) Is the new managerial model adopted by the State, after its administrative reform in 1998, in consequence of Constitutional Amendment Number 19, compatible with all citizen victories in constitution in 1988? 4) How to make it part of the constitution in the denominated Third Sector and/or make it compatible with the constitutional text? 5) Can its participation be considered more efficient than of the State, and under this fundament, in some cases, replace entirely the execution of state public policies? And therefore, in order to face these five big issues, we go back to the origins of the Third Sector; its concepts; its functions of Welfare State and of the role assumed by society of Social Welfare; by the presentation of the Third Sector in the constitutional order; by the important role of constitutional interpretation by this Sector; by its state regulation and by the examination of its great challenge: growth and development of the Third Sector and of Human Rights